PENGARUH KEDISIPLINAN SISWA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA SWASTA DEPOK - Sugeng , Haryono (Faktor Jurnal Ilmiah Kependidikan, 2016)
The purpose of this study was to analyze the impact of the effect of student discipline and learning motivation toward learning achievement on economic subjects Private high school students in Depok. The experiment was conducted on students of class XI social science education programs (IPS). The method used is survey method with correlation analysis techniques. Of class XI in SMA Sejahtera 1, SMA Open 4, and senior IT Nururrahman, each school is taken by the same amount or almost the same, while the election of each school is done randomly. The research sample of 120 students were taken acak. Keywords : Discipline , motivation , learning interpretation . SMA